2002
DOI: 10.1136/pmj.78.920.344
|View full text |Cite
|
Sign up to set email alerts
|

Older people and ill fitting shoes

Abstract: Background: Foot health is an important issue in older people. Inappropriate shoes increase the risk of callous and ulcer formation, as well as increasing the risk of falls. There are no data defining the size of this problem. Objective: The aim of the study was to investigate the proportion of elderly people on a general rehabilitation ward wearing incorrectly sized shoes and to look for the presence of complications. Methods: Sixty five consecutive patients (mental state questionnaire score >6) admitted to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
88
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(107 citation statements)
references
References 12 publications
(11 reference statements)
19
88
0
Order By: Relevance
“…These outcomes highlight the potential burden of foot disease within the rapidly expanding Australian subacute inpatient sector and forecast the need to ensure evidence-based foot disease management is available in subacute inpatient rehabilitation facilities to prevent acute inpatient re-admission and amputation. The prevalence of foot disease in this subacute inpatient population were similar, and in some cases higher, than those reported in other at risk populations for foot disease and other smaller subacute inpatient studies [15][16][17][18][19][20][21][22][23]. For example active foot disease prevalence reported in this study via current foot ulcers (12%) appears to broadly align with the foot ulcer prevalence reported in two other smaller subacute inpatient studies [22,23]; foot ulcer prevalence in those studies were 7% (Australian study) [22] and 15% (UK study) [23].…”
Section: Discussionsupporting
confidence: 70%
“…These outcomes highlight the potential burden of foot disease within the rapidly expanding Australian subacute inpatient sector and forecast the need to ensure evidence-based foot disease management is available in subacute inpatient rehabilitation facilities to prevent acute inpatient re-admission and amputation. The prevalence of foot disease in this subacute inpatient population were similar, and in some cases higher, than those reported in other at risk populations for foot disease and other smaller subacute inpatient studies [15][16][17][18][19][20][21][22][23]. For example active foot disease prevalence reported in this study via current foot ulcers (12%) appears to broadly align with the foot ulcer prevalence reported in two other smaller subacute inpatient studies [22,23]; foot ulcer prevalence in those studies were 7% (Australian study) [22] and 15% (UK study) [23].…”
Section: Discussionsupporting
confidence: 70%
“…Although feet that are structurally sound can perform daily tasks with ease, deviations from normal foot structure can compromise foot function and, in turn, cause discomfort and/or pain [6]. Extensive research has confirmed that overweight and obesity negatively affect foot structure and function in children, whereby obese children have been found to have flatter feet and generate significantly higher plantar pressures during walking relative to non-overweight children [7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Shoe sizing changes have been previously reported within running shoes where the marketed size is not representative of the actual size of the shoe [30]. If consumers are not aware of this sizing error, shoes that are too small or big could be worn without any knowledge by the user contributing to potential pathology [7].…”
Section: Footwear Characteristicsmentioning
confidence: 99%
“…A shoe that is either too loose or too tight can also influence comfort with tissue compression in a snug shoe and slippage or friction in a larger shoe [4]. Observations on shoe wearing habits in the elderly indicates that up to 72% wear shoes that are ill-fitting associated to foot pain and ulceration [7]. Despite the strong evidence to support the notion that ill-fitting footwear can cause foot pain and ulceration, people continue to wear shoes that do not fit the foot [8].…”
Section: Introductionmentioning
confidence: 99%